Making Information Infrastructure Work (In)visible As University Campuses Reopen - Snider, Madison (2020)
ABSTRACT The impact of COVID-19 on university campuses has largely centered on student experiences and overlooked others for whom the campus is a worksite, including the combined efforts of IT (information technology) and Facilities teams who have continued working to maintain critical information infrastructures. Growing concerns about the invasiveness of new protocols that rely on biometric data collection and tracking, while merited, may miss the more naturalized forms of worker surveillance that accompany such maintenance work. These surveillance apparatuses predate COVID-19. This paper will argue, that COVID-19 responses in the workplace leverage existing surveillance apparatuses. Emergent findings on the implementation and maintenance of information infrastructures and requisite changes to university workflows due to the pandemic, the paradox of (in)visible labor can be conceptualized anew with insights into the potential risks of greater worker surveillance. Keywords Information infrastructure, labor visibility, universities, COVID-19 ABOUT THE AUTHOR/S Madison Snider University of Washington msnid@uw.edu I am a PhD Candidate at the University of Washington in the Department of Communication. I am a qualitative researcher interested in locating power in critical infrastructure systems. I am particularly interested in processes of sociotechnical change through which we can observe and make sense of the workings of power. https://www.linkedin.com/in/madison-snider-91a83385/ New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).